EFEKTIVITAS PENGGUNAAN BIOKOAGULAN DALAM MENINGKATKAN KUALITAS AIR SUMUR: SYSTEMATIC LITERATURE REVIEW - Kamsul Kamsul; Jerni Puspita Shatara; Maya Sopianti; Muhammad Habib; Iqbal Pebrilasyah; Agnes Wulandari (Jurnal Sanitasi Profesional Indonesia, 2025)
The availability of abundant groundwater and easy access are the main reasons why people rely on well water to meet their daily needs. However, the use of well water without adequate treatment has the potential to pose a health risk considering that the quality of groundwater is greatly influenced by environmental conditions such as waste pollution. This study aims to examine several preferences for natural coagulants used to improve the quality of well water so that they have the potential to replace synthetic coagulants which are known to have negative impacts on health. The method used in this study is a Systematic Literature Review sourced from the Google Scholar database through the Publish or Perish and Mendeley applications. Based on the results of the review of literature relevant to the topic, it was found that biocoagulants sourced from pineapple skin, a combination of tamarind and mangrove roots, aloe vera and winged bean seeds have been proven to be effective in improving the quality of well water by reducing turbidity levels and the content of metal compounds (Fe) and dangerous anions (Cl). Thus, well water that has gone through a purification process has the potential to be used as clean water to meet daily needs. Keywords: Well water; Biocoagulant; Water quality; Pollution; Sanitation